Influence of leader sense-giving and leader promotion of team sense-making on team effectiveness: mediation role of team planning and team adaptation - Marras, V.; Passos, A. M. (19th EAWOP Congress, 2019)
Purpose: This study aims to analyze the effect of two leadership functions, leader sense-giving (LSG) and leader promotion of team sense-making (LPSM) on team effectiveness, measured through team performance. The study also analyses the mediation role in this relationship of both deliberate and contingency planning and team adaptation Design/Methodology: We tested our model with a sample of 82 teams (304 team members and 81 team leaders) from consultancy firms. Data was collected through two different survey questionnaires: one for team members and one for leaders. Results: Deliberate planning and team adaptation positively mediate the relationship between LSG (B = 0.22, CI = 0.09, 0.37) and LPSM (B = 0.24, CI = 0.10, 0.40) on team performance. Contingency planning and team adaptation positively mediate the relationship between LSG (B = 0.24, CI = 0.09, 0.40) and LPSM (B = 0.25, CI = 0.10, 0.43) on team performance. Limitations: Given the self-reported nature of data and the use of a common scaling approach, limitations exist regarding the applicability and extendibility of results of this study. Research/Practical Implications: Teams need to include deliberate and contingency planning in their routine, as it positively impacts their capacity to adapt and consequently their performance. Leaders need to be trained in engaging in and choosing between LSG and LPSM functions in order to guide their team towards effective planning and adaptation processes. Originality/Value: This study introduces a new leadership function, leader promotion of team sense-making, and analyses its influence on team effectiveness.